Common Priority Map for Selection History, Reward and Emotion in the Oculomotor System. (August 2015) - Belopolsky, Artem V.
In natural scenes, many objects compete for visual selection. However, it is not always clear why certain objects win this competition. I will demonstrate that the eye movement system lives in a constant state of competition among different oculomotor programs. This competition is not limited to the competition between the current goals of the observer and salient objects in the environment but incorporates independent influences from memory, reward, and emotional systems. These involuntary and automatic biases often overcome the goal-directed selection and expose severe limits in goal-driven control. There is also a striking similarity in the way that these very different sources of bias activate the oculomotor system and compete for representation. The inputs from various information sources are integrated in the common map in the oculomotor system for the sole purpose of improving the efficiency of oculomotor selection.